The morphologic evaluation of the mucosa of urinary bladder in hyperthyroid and hypothyroid state [Hipotiroidi ve hipertiroidi oluşturulmuş siçanlarda mesane mukozasinin morfolojik olarak in incelenmesi] - (:unkn) unknown (My University, 2003)
Introduction: There is limited number of studies related to the effects of thyroid hormones on urinary bladder. Most of these studies concern about the physiologic effect of those hormones on urinary bladder. We studied the epithelial morphology of bladder under the influence of thyroid hormones. Materials and methods: Three groups were set, a) Control group, b) Hypothyroidy group, c) Hyperthyroidy group. At the end of the experiment, tissues were obtained for routine histologic preparation both for light and electron microscopy. Results: Light microscopy revealed regular mucous disribution in hypothyroidy over lamina propria. Electron microscopy showed expansion of intercellular spaces severe in hypothyroidy and moderate in hyperthyroidy. Endothelial blebs protruding through endothelium, into the capillary lumen was observed in hyperthyroidy group. Conclusions: As a result hypotyhroidy exerts serious morphologic effects on urinary bladder such as intercellular detachments in the epithelium and change in collagen distribution which may lead to cystitis. When lower urinary tract symptoms (LUTS) with unknown etiology are present, thyroid hormone disorders must be taken into consideration and for the same reason in cases of thyroid disorders, patients should be questioned about LUTS.
Keywords: Microscopy; Morphology; Thyroid hormones; Urinary bladder